2018
DOI: 10.2147/ott.s156810
|View full text |Cite|
|
Sign up to set email alerts
|

miR-622 suppresses tumor formation by directly targeting VEGFA in papillary thyroid carcinoma

Abstract: BackgroundMicroRNAs (miRNAs) were reportedly to play crucial roles in papillary thyroid carcinoma (PTC) tumorigenesis and development. Therefore, the discovery of miRNAs may provide a new and powerful tool for diagnosis and treatment of PTC.PurposeThe aim of this study was to investigate the biological function and underlying mechanism of miR-622 in PTC.Materials and methodsThe expression levels of miR-622 in PTC patient tissues and cell lines were determined by quantitative RT-PCR (qRT-PCR). The biological fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 25 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Recent studies have demonstrated that numerous miRNAs are dysregulated in PTC 3639. The dysregulated miRNAs and their direct target genes consist of a complex network, which are implicated in the initiation and progression of PTC by regulating a range of biological processes 4042.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that numerous miRNAs are dysregulated in PTC 3639. The dysregulated miRNAs and their direct target genes consist of a complex network, which are implicated in the initiation and progression of PTC by regulating a range of biological processes 4042.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that miR-622 acts as a tumour suppressor in several types of human cancer such as glioma, 10 , 11 gastric, 12 , 13 pancreatic, 14 hepatocellular 15 thyroid 16 and oesophageal squamous cell carcinomas, 17 where it affects cell proliferation, migration and metastasis. Additionally, miR-622 suppresses migration and invasion of colorectal cancer cells by targeting K-RAS 18 and DYRK2.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia and neovascularization are major pathological mechanisms in HCC driving progression and therapy resistance [51] , [52] , [53] , [54] , and current first-line therapeutic concepts in HCC (sorafenib, lenvatinib, bevacizumab) majorly target the hypoxia-associated VEGF-tumor-vascularization-axis [ 53 , 55 ]. Moreover, miR-622 was directly linked with hypoxia, VEGF-signaling and (neo-)vascularization in several cancer types including colorectal cancer [ 42 , 56 , 57 ]. In this regard, we found that the novel and yet undescribed target gene of miR-622 in liver cancer, ZCCHC11, was strongly correlated with hypoxia inducible factor 1, angiopoietin 2 and VEGFA in human HCC tissues.…”
Section: Discussionmentioning
confidence: 99%